2017
DOI: 10.3126/jpan.v5i1.18324
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in Schizophrenia: Current Perspective

Abstract: Impairments in a variety

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Cognitive impairments are frequently moderate to a serious degree, seem to present across the life span, stable over time, obvious at the time of the first episode of illness and most likely originate before the disorder (Aich et al, 2016). It has been found that the cognitive impairments most commonly described in patients with schizophrenia comprise processing speed, attention, visual and verbal learning, working memory, abstract thinking, problem solving and social cognition (Kaneko, 2018; Marder, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive impairments are frequently moderate to a serious degree, seem to present across the life span, stable over time, obvious at the time of the first episode of illness and most likely originate before the disorder (Aich et al, 2016). It has been found that the cognitive impairments most commonly described in patients with schizophrenia comprise processing speed, attention, visual and verbal learning, working memory, abstract thinking, problem solving and social cognition (Kaneko, 2018; Marder, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Almost all patients with schizophrenia are undermined in their capacity to function in the community because of cognitive impairment (Aich et al, 2016; Bowie & Harvey, 2006). Therapeutic modalities for cognitive impairment include pharmacological treatments and cognitive remediation.…”
Section: Introductionmentioning
confidence: 99%